Interferon-associated therapies toward HIV control: The back and forth. (April 2018) - Noël, Nicolas; Jacquelin, Béatrice; Huot, Nicolas; Goujard, Cécile; Lambotte, Olivier; Müller-Trutwin, Michaela
Graphical abstract: Highlights: Overview of the results obtained with IFN type I – based therapies from the early days of the HIV pandemic up to now. Lessons drawn from previous IFN type I – associated pre-clinical and clincial studies. Overview of innovative strategies for optimizing the antiviral action of IFN-I. Combination of IFN type I - based therapies with other anti-viral or immunomodulatory agents in the context of HIV cure. Overview of attempts to counteract IFN-I in view of reducing HIV-induced inflammation. Abstract: Human immunodeficiency virus (HIV) induces a persistent and incurable infection. However, the combined antiretroviral treatment (cART) has markedly changed the evolution of the infection and transformed a deadly disease into a manageable chronic infection. Withdrawal of cART generally leads though to resumption of the viral replication. The eradication of the virus from its cellular and anatomical reservoirs remains a goal-to-achieve for a cure. In this context, developing novel therapies contributing to this aim are an important field of research. Type I IFN has antiviral activity, which, before the presence of efficient anti-HIV drugs, has led to the testing of IFN-based therapeutic strategies during the early years of the pandemic. A historical overview of the results and its limitations that were put into light are reviewed here. In addition, several lessons could be drawn. For instance, the efficacy of the IFN-I depends on the timing of its administration and the context. Thus, the persistence of an endogenous IFN-signature, such as that generally observed in viremic patients, seems to be associated with a lower efficacy of IFN. Based on the lessons from previous trials, and in the context of cART and research for a cure, type I Interferon has regained interest and novel therapeutic approaches are currently tested in combination with cART, some with disappointing, other with encouraging results with regard to a reduction in the size of the HIV reservoir and/or delays in viral rebound after cessation of cART. Additional strategies are currently developed in addition to improve the antiviral function of the IFN-I, by using for instance other IFN subtypes than IFN-Iα2. In parallel, the development of innovative strategies aimed at counteracting the excessive activation of the IFN-pathways have been continued and their results are reviewed here as well. Altogether, the use of IFN-I in anti-HIV therapies has gone through distinct phases and many lessons could be drawn. Novel combinations are currently be tested that might provide interesting results.